The Formation of Carbon Microcoils Having the Coil-Type Overall Geometry - Kang, Gi-Hwan; Kim, Sung-Hoon (Journal of Coating Science and Technology, 2016)
Carbon microcoils could be synthesized using a thermal chemical vapor deposition process in which C2H2/H2 is used as the source gas and SF6 as an additive gas. We investigated the formation of carbon microcoils as a function of reaction time to study the growth mechanism of coil-type carbon microcoils, particularly under long reaction time. After the first 5 min of the reaction, wave-like carbon nanocoils were formed along with carbon microcoils at certain positions on the sample. An increase in reaction time (60 min) led to the formation of double helix-type carbon microcoils. Further increase in the reaction time (120 min) led to the formation of twist-type carbon microcoils with occasional growth of the coil-type carbon microcoils on the sample. However, at the longest reaction time (180 min) investigated in this work, we observed a decrease in the density of the carbon microcoils. Based on these results, we determine the optimal reaction time for the growth of double helix-type carbon microcoils and suggest the growth mechanism of the coil-type carbon microcoils with a focus on long reaction time.